Pengaruh Sikap Fanatisme, Brand Ambassador Dan Perilaku Konsumtif Terhadap Keputusan Pembelian Pada Produk Chatime X Jkt 48 Di Bekasi - Puspita Sari Dewi; Nur Fitri Rahmawati (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. The collaboration between Chatime and JKT48 is a marketing strategy that leverages the power of fan communities and emotional closeness to drive purchase decisions. This phenomenon shows that fan loyalty can be utilized through emotional and digital approaches to increase sales. This study aims to analyze the influence of Fanatic Attitude, Brand Ambassador, and Consumptive Behavior on Purchase Decisions of Chatime X JKT48 products in Bekasi. The research employed a quantitative method with a survey technique, where data were collected through questionnaires distributed to consumers who had purchased the collaboration products. The analysis was conducted using multiple linear regression. The results indicate that the three independent variables have a positive and significant influence, both partially and simultaneously. Brand Ambassador has the most dominant effect at 47.0%, followed by Consumptive Behavior at 42.0% and Fanatic Attitude at 39.1%. Collectively, the three variables contribute 57.7% to purchase decisions. Keywords:Fanaticism Attitude, Brand Ambassador, Consumer Behavior, Purchase Decision, Chatime X JKT48